Al-Farabi's Philosophical Thoughts - Muhammad Adhil Fatih Nasrullah; Dina Solehah; Gina Mardilah; Fattahu Rahman; Euis Latipah (Penerbit Hellow Pustaka, 2025)
Islamic philosophy is a systematic study of life, the universe, ethics, morality, science, thought and political thought in Islamic civilization which is related to Islamic teachings. The existence of a world-renowned philosopher named Al-Farabi is one of the figures who brought about epoch-making events in Islamic philosophy by subsequent philosophers. The world is illuminated by his works, such as the emanations and philosophy of Al-Farabi’s soul, becoming the vanguard of the next generation of Muslims. A prominent Muslim philosopher of the 9th century. Al-Farabi played an important role in the development of Islamic philosophy. According to Al-Farabi, philosophy is a science that studies truth, goodness and justice. For Al-Farabi, philosophy is not just a theory, but also a way of life that includes an understanding of the universe, the purpose of life, and how to achieve happiness and perfection. He considers that philosophy is a form of knowledge that guides humans towards moral and intellectual perfection.